Associations of short-term exposure to ambient air pollutants with emergency ambulance calls for the exacerbation of essential arterial hypertension. Issue 6 (2nd November 2017) - Vencloviene, Jone; Braziene, Agne; Dedele, Audrius; Lopatiene, Kristina; Dobozinskas, Paulius
Abstract: We investigated the association between daily emergency ambulance calls (EAC) for elevated blood pressure that occurred during the time intervals of 8:00–13:59, 14:00–21:59, and 22:00–7:59, and exposure to CO, PM10, and ozone. We used Poisson regression to explore the association between the risk of EAC and short-term variation of pollutants, adjusting for seasonality and weather variables. Before noon, the risk was associated with an interquartile range (IQR) (7.9 μg/m 3 ) increase in PM10 at lag 2–4 days below the median (RR = 1.08, p  = 0.031) and with an IQR (0.146 mg/m 3 ) increase in CO at lag 6–7 below the median (RR = 1.05, p  = 0.028). During 14:00–21:59, the risk was associated with an IQR (18.8 μg/m 3 ) increase in PM10 on the previous day below the median (RR = 1.04, p  = 0.031). At night, EAC were negatively affected by lower O3 (lag 0–2) below the median (per IQR decrease RR = 1.10, p  = 0.018) and a higher PM10 at lag 0–1 above the median for the elderly (RR = 1.07, p  = 0.030).